Um estudo psicanalítico dos Narcóticos Anônimos - Salim, Anna Luiza Dantas (2019)
This work carried out a Lacanian orientation study of the mutual aid group Narcotics Anonymous (NA) through the analysis of its institutional literature. The first theoretical chapter addressed the psychoanalytic concept of drug addiction, in its relations with the concepts of drive, enjoyment and identification. The second theoretical chapter presented the different axes and ethics of treatment of drug addiction from the Lacanian theory of discourses. The third theoretical chapter characterized the logic of abstinence and the logic of treatment of the subject in drug addiction. For the analysis of data, the applied psychoanalysis method was used. The fifth chapter deals with the specificities of this research method. The sixth chapter covers the presentation and analysis of results. Four fundamental elements were found for the therapy of NA: the conception of addiction, the program and the spiritual principles, the relation with another addict and the relation with the Higher Power. The main foundations of NA therapy found in their institutional literature were: the obedience to S1, imaginary substitution promoted by horizontal identification with another addict, the focus given to the I conceived as an imaginary instance capable of managing one's own enjoyment and belief in Power Superior, exercising the function of vertical identification and psychic shelter. The results indicate that NA therapy is based on the master's discourse, having as S1 the program, which encompasses the 12 Steps and the Twelve Traditions, as S2 the "recovering addict", possessing a knowledge about the surplus enjoyment of the drug and whose production is linked to the drug (a) as a surplus enjoyment object, although in a negative way as abstinence and that the covered truth of the NA discourse is that of the ideology of the self-made man.